The Theatrics of Religious Gymnastic in White Garment Church; Wole Soyinka’s The Trials of Brother Jero’s Performance as Directed by Ade Adeseke in Focus - Josiah Adewale Apalowo; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
Religion in Africa functions not only as a system of spiritual beliefs but also as a cultural performance deeply embedded in social practices. In many African Indigenous churches, particularly the white garment churches—religious expression frequently transcends conventional worship through stylised bodily movements, choreographed dances, and the incorporation of secular songs. While these practices are captivating and energising, they often lack explicit spiritual significance and instead serve to entertain, unify congregants, and cultivate a shared religious identity. This study critically examines Ade Adeseke’s stage direction of Wole Soyinka’s The Trials of Brother Jero as a lens through which to explore the performative dynamics of religious expression within these church contexts. By employing performance theory as its analytical framework, the study interrogates the intersection of theatricality and spirituality, revealing how certain churches employ spectacle and performative strategies not solely for worship but as mechanisms of attraction, inclusion, and socio-cultural resonance. The research adopts a qualitative methodology, with data gathered through content analysis of both the dramatic text and relevant performance recordings. Findings suggest that Adeseke’s rendition of Soyinka’s satire offers a compelling critique of how performance can be manipulated to simulate divine presence, blur the lines between the sacred and the secular, and reinforce systems of power and deception within religious spaces. Ultimately, the study concludes that such performative elements, while engaging, often compromise the authenticity of spiritual experience, thereby transforming worship into theatrical display.